Facial emotion decoding in patients with Parkinson's disease. (2nd January 2018) - De Risi, Marco; Di Gennaro, Giancarlo; Picardi, Angelo; Casciato, Sara; Grammaldo, Liliana G.; D'Aniello, Alfredo; Lanni, Deborah; Meletti, Stefano; Modugno, Nicola
ABSTRACT: Purpose . In line with the growing attention on non-motor symptoms and disturbance of affective and emotional processing in Parkinson's disease, we aimed to study the different aspects of facial emotion expression evaluation in a group of Parkinson's disease without cognitive decline in treatment with common antiparkinsonian drugs, matched for sex, age and education with healthy subjects. Materials and methods. The study was conducted on 30 patients (13 male; mean age: 63.3 ± 6.7; mean age of disease onset: 56.5 ± 7.1; mean duration of the disease: 6.7 ± 2.6) with a diagnosis of Parkinson's disease and receiving dopaminergic therapy, as compared with 30 healthy controls. Different tasks of facial expression evaluation were used. All patients were assessed for neuropsychological and psychological profiles during optimized medication-on condition. Results. The total number of errors in facial emotion recognition task is higher ( p < 0.001) in patients than controls and it is due to errors in identifying sadness ( p < 0.001), anger ( p = 0.01) and fear ( p < 0.001). No differences in the total amount of activation, valence and intensity ratings were found. The difference between patients and controls in emotion recognition appears to be independent by the severity of depressive symptoms. Conclusions. The present study provides further evidence of altered non-verbal emotional information processing in Parkinson's disease patients, suggesting that nigrostriatal dopaminergic depletion leads also to emotional information processing dysfunction. The consequences of these emotional encoding disturbances in daily living and their relationship to mood and behavioural disorders remain to be clarified.